2002
DOI: 10.1083/jcb.200208037
|View full text |Cite
|
Sign up to set email alerts
|

Signal recognition particle RNA localization within the nucleolus differs from the classical sites of ribosome synthesis

Abstract: The nucleolus is the site of ribosome biosynthesis, but is now known to have other functions as well. In the present study we have investigated how the distribution of signal recognition particle (SRP) RNA within the nucleolus relates to the known sites of ribosomal RNA synthesis, processing, and nascent ribosome assembly (i.e., the fibrillar centers, the dense fibrillar component (DFC), and the granular component). Very little SRP RNA was detected in fibrillar centers or the DFC of the nucleolus, as defined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 38 publications
3
59
0
Order By: Relevance
“…In parallel experiments it was observed that oligo(dT) or oligo(dA), or oligos containing repeating CTG or CAG sequences did not concentrate in the nucleolus, and in fact, appeared to be excluded from the nucleolus ( Figure 2B and our unpublished results). In standard in situ hybridization experiments with fixed cells, the 28S antisense oligos generated signal in the nucleolus and the cytoplasm as expected ( Figure 2C; see also Politz et al, 2002), whereas only background levels of signal were detected with control oligos ( Figure 2D). J.C.R.…”
supporting
confidence: 73%
See 4 more Smart Citations
“…In parallel experiments it was observed that oligo(dT) or oligo(dA), or oligos containing repeating CTG or CAG sequences did not concentrate in the nucleolus, and in fact, appeared to be excluded from the nucleolus ( Figure 2B and our unpublished results). In standard in situ hybridization experiments with fixed cells, the 28S antisense oligos generated signal in the nucleolus and the cytoplasm as expected ( Figure 2C; see also Politz et al, 2002), whereas only background levels of signal were detected with control oligos ( Figure 2D). J.C.R.…”
supporting
confidence: 73%
“…Oligodeoxynucleotides complementary to these five regions of 28S rRNA, each 33 nucleotides in length, were synthesized with four, approximately evenly spaced aminohexyl-modified thymidines (see MATERIALS AND METHODS), and these sites were labeled with fluorescein as described Politz et al, 2002). RNA hybrids formed with oligos labeled in this manner are less susceptible to degradation in vivo, perhaps because the evenly spaced aminohexyl arms interfere with RNase H binding (Ueno et al, 1997;J.C.R.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations